2015
DOI: 10.1103/physreva.92.032311
|View full text |Cite
|
Sign up to set email alerts
|

Distributed correlations and information flows within a hybrid multipartite quantum-classical system

Abstract: Understanding the non-Markovian mechanisms underlying the revivals of quantum entanglement in the presence of classical environments is central in the theory of quantum information. Tentative interpretations have been given by either the role of the environment as a control device or the concept of hidden entanglement. We address this issue from an information-theoretic point of view. To this aim, we consider a paradigmatic tripartite system, already realized in the laboratory, made of two independent qubits a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 65 publications
0
45
1
1
Order By: Relevance
“…Later this phenomenon was extended to bipartite or multipartite systems interacting with different kinds of dissipative environments [8][9][10][11][12][13]. At the same time, revival of entanglement in open quantum systems was predicted and observed under suitable environmental conditions [14][15][16][17][18][19][20]. For instance, Xu et al [17] experimentally showed recovery of quantum correlations in classical environments without system-environment back-action.…”
Section: Introductionmentioning
confidence: 95%
“…Later this phenomenon was extended to bipartite or multipartite systems interacting with different kinds of dissipative environments [8][9][10][11][12][13]. At the same time, revival of entanglement in open quantum systems was predicted and observed under suitable environmental conditions [14][15][16][17][18][19][20]. For instance, Xu et al [17] experimentally showed recovery of quantum correlations in classical environments without system-environment back-action.…”
Section: Introductionmentioning
confidence: 95%
“…There are many works in quantum information literature focused on RTN [66][67][68][69][70][71][72] or 1/ f noises [68,[73][74][75][76][77][78][79], but few studies are available for 1/ f 2 noise [61,[80][81][82]. The exploration of these kinds of noises is of utmost importance for practical applications, since the system can exhibit peculiar phenomena (like sudden death and revival of correlations, or memory effects) as a function of the noise spectrum [83][84][85], even for classical noise sources [61,66,[86][87][88][89][90] such as RTN fluctuators. 1 For what concerns QWs, many studies are devoted to noise in discrete-time quantum walks, but for continuous-time quantum walks there is a limited amount of studies [91,92], which are concerning, e.g., static noise [93], RTN [66,94] or other mechanisms of decoherence, such as phonon thermal baths (see [95] and cited references), unitary noise [96], measurements [97] and lattice defects [98].…”
Section: Introductionmentioning
confidence: 98%
“…Classical environments, however, can have "effective" back-action on a physical system, as recently shown[61,66,[86][87][88][89][90], thus determining a revival of quantum correlations.…”
mentioning
confidence: 97%
“…In this context much effort has been devoted to engineer those undesired effects in order to minimize the degrading effects [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. Sim-15 ilarly, a great interest has emerged in the scientific community to characterize the physical bounds and the kind of states, which, despite their mixture degree, are able to manifest quantum features.…”
Section: Introductionmentioning
confidence: 99%